Conoscere per deliberare. Riflessioni sulla formazione giuridica (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. Breve storia delle riforme universitarie a) fino al 2000 - 3. b) dal 2000 a oggi - 4. Il piano degli studi giuridici e l’accesso alle “professioni classiche” - 5. Proposte di revisione della tabella attuale. a) il contesto generale e particolare - 6. b) i punti salienti.Knowing to deliberate. Reflections on legal education.ABSTRACT: The debate on legal education in Italy appears to be an always open question. The synthesis is complicated by the coexistence of multiple factors that increase its complexity. However, the gradual and stable decrease in enrollments and the simultaneous lack of employment prospects for graduates require it to be revised, also favored by the opportunities opened by the National Recovery and Resilience Plan (PNRR). In this essay I proceed to a preliminary historical reconstruction of the debate still in progress and I present reflections which, hopefully, will be useful for its operational conclusion.